PLC Controlled Fuzzy Logic-Based Egg Hatching Machine - Eltaleb, Muhammed; Çelik, Hakan (My University, 2024)
In response to the increasing food demand due to the growing global population, this study has designed a fully automated incubator machine based on a Programmable Logic Controller (PLC) to enhance efficiency in the egg production sector. To align with Industry 4.0 technologies, this machine controls temperature and humidity using fuzzy logic, one of the artificial intelligence methods. The incubator is capable of meeting the specific temperature and humidity needs for the incubation processes of various types of bird eggs. It has been tested under different conditions, and its performance has been examined in detail. The analysis results show that the fuzzy logic-based temperature and humidity control systems on the PLC successfully reached the set reference values and maintained them continuously and stably after initial fluctuations. In conclusion, the design and control of an automated incubation machine with a PLC-based fuzzy logic controller were successfully accomplished.
Keywords: Fuzzy logic; Industry 4.0; Programmable logic controller; temperature control; humidity control.